Laparoscopic cholecystectomy after endoscopic trans-papillary gallbladder stenting for acute cholecystitis: a pilot study of surgical feasibility - Fumihiro Kawano (BMC Surgery, 2021)
Abstract Background Percutaneous transhepatic gallbladder drainage (PTGBD) is indicated for patients with acute cholecystitis (AC) who are not indicated for urgent surgery, but external tubes reduce quality of life (QOL) while waiting for elective surgery. The objective of the present study was to investigate the feasibility of laparoscopic cholecystectomy after endoscopic trans-papillary gallbladder stenting (ETGBS) comparing with after PTGBD. Methods Intraoperative and postoperative outcomes of patients with ETGBS and PTGBD were retrospectively compared. Results Eighteen ETGBS and ten PTGBD patients were compared. Differences in the duration of ETGBS and PTGBD [median 209 min (range 107–357) and median 161 min (range 130–273), respectively, P = 0.10], median blood loss [ETGBS 2 (range 2–180 ml) and PTGBD 24 (range 2–100 ml), P = 0.89], switch to laparotomy (ETGBS 11% and PTGBD 20%, P = 0.52), and median postoperative hospital stay [ETGBS 8 (range 4–24 days) and ETGBS 8 (range 4–16 days), P = 0.99]. Thickening of the cystic duct that occurred in 60% of the ETGBS patients and none of the PTGBD patients (P = 0.005) interfered with closure of the duct by clipping. No obstruction occurred in ETGBS patients. Conclusion ETGBS did not make laparoscopic cholecystectomy less feasible than after PTGBD. This is a pilot study, and further investigations are needed to validate the results of the present study.